Discourse accessibility constraints in childrenʼs processing of object relative clauses - Haendler, Yair; Kliegl, Reinhold; Adani, Flavia (Frontiers in Psychology, 2015)
Childrenʼs poor performance on object relative clauses has been explained in terms of intervention locality. This approach predicts that object relatives with a full DP head and an embedded pronominal subject are easier than object relatives in which both the head noun and the embedded subject are full DPs. This prediction is shared by other accounts formulated to explain processing mechanisms. We conducted a visual-world study designed to test the off-line comprehension and on-line processing of object relatives in German-speaking 5-year-olds. Children were tested on three types of object relatives, all having a full DP head noun and differing with respect to the type of nominal phrase that appeared in the embedded subject position: another full DP, a 1st- or a 3rd-person pronoun. Grammatical skills and memory capacity were also assessed in order to see whether and how they affect childrenʼs performance. Most accurately processed were object relatives with 1st-person pronoun, independently of childrenʼs language and memory skills. Performance on object relatives with two full DPs was overall more accurate than on object relatives with 3rd-person pronoun. In the former condition, children with stronger grammatical skills accurately processed the structure and their memory abilities determined how fast they were; in the latter condition, children only processed accurately the structure if they were strong both in their grammatical skills and in their memory capacity. The results are discussed in the light of accounts that predict different pronoun effects like the ones we find, which depend on the referential properties of the pronouns. We then discuss which role language and memory abilities might have in processing object relatives with various embedded nominal phrases.